2018
DOI: 10.1016/j.physleta.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Shannon entropies and Fisher information of K-shell electrons of neutral atoms

Abstract: We represent the two K-shell electrons of neutral atoms by Hylleraas-type wave function which fulfils the exact behavior at the electron-electron and electron-nucleus coalescence points and, derive a simple method to construct expressions for single-particle position-and momentum-space charge densities, ρ(r) and γ(p) respectively. We make use of the results for ρ(r) and γ(p) to critically examine the effect of correlation on bare (uncorrelated) values of Shannon information entropies (S) and of Fisher informat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…[ 48 ] For a wavefunction that includes several terms of r 12 , it is appropriate to employ the Hylleraas coordinates. [ 22,29,32–35,39–42,44–46,49,50 ]…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 48 ] For a wavefunction that includes several terms of r 12 , it is appropriate to employ the Hylleraas coordinates. [ 22,29,32–35,39–42,44–46,49,50 ]…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[48] For a wavefunction that includes several terms of r 12 , it is appropriate to employ the Hylleraas coordinates. [22,29,[32][33][34][35][39][40][41][42][44][45][46]49,50] In the present study, we used the two-parameter wavefunction as suggested by the entangled, or non-separable, wavefunction:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, it is one measure of the position‐momentum correlation . It has been studied in a variety of models, fermionic and bosonic systems including Bose‐Einstein condensates . Its N‐dependence has also been used to support the theory of gravity as emergent phenomena …”
Section: Introductionmentioning
confidence: 99%